Leadership and conflict : tensions in medieval and early modern Jewish history and culture - Saperstein, Marc (Littman library of Jewish civilization (Series), 2014)
"This is a collection of the author's essays, some previously published, all freshly edited for this volume. It is a multifaceted analysis of how Jewish leaders in medieval and early modern times responded to the challenges they faced. Based largely on the study of sermons and response -- genres that show Jewish leaders addressing real situations in the lives of their people -- it reveals how rabbis have handled intellectual, social, and political diversity and conflict in various vibrant Jewish communities"--